AGREEMENT BETWEEN PHYSICAL BEST AND FITNESSGRAM CRITERION-REFERENCED STANDARDS FOR MUSCULAR STRENGTH AND ENDURANCE - Gustavo Aires de Arruda; Diogo Henrique Constantino Coledam; Francys Paula Cantieri; Arli Ramos de Oliveira (Sociedade de Pediatria de São Paulo, 2021)
ABSTRACT Objective: To verify the agreement between PHYSICAL BEST and FITNESSGRAM health-related criteria for muscle strength and endurance. Methods: This agreement study had a sample of 81 children and adolescents. Participants were submitted to the PHYSICAL BEST (Sit-up and Pull-up) and FITNESSGRAM (Curl-up and Modified Pull-up) test batteries. Additionally, FITNESSGRAM also proposed criteria for Pull-up test. Results of tests were classified in accordance with their respective criteria. Each group had an interval of seven days between the first and second battery of tests. Statistical analysis used the Kappa index (p<0.05). Results: Sit-up and Curl-up tests among the boys agreed in 72.2% (Kappa=0.368; p=0.004) of cases, and for the girls, in 64.4% (Kappa=0.130; p=0.076). Pull-up (PHYSICAL BEST versus FITNESSGRAM) agreed in 83.3% (Kappa=0.599; p<0.001) for boys. The agreement between Pull-up and Modified Pull-up (PHYSICAL BEST versus FITNESSGRAM) for boys was 47.2% (Kappa=0.071; p=0.533), and for girls, 44.5% (Kappa=0.102; p=0.120). The agreement between the Pull-up and Modified Pull-up tests (FITNESSGRAM) for boys was 58.4% (Kappa=0.215; p=0.143), and for girls, 44.5% (Kappa=0.102; p=0.120). Conclusions: For individual analysis over time, as well as for the comparison of passing rates between different populations, caution is advised when using different criterion-referenced standards for strength and endurance, particularly if using different tests.